Subjective wellbeing components among non-procedural blue collar Indonesian migrant worker: How international migration shapes their perspective - Rusli, Adi Saputra; Hanita, Margaretha; Murni, Sri (Indonesian Journal of Multidisciplinary Science, 2024)
The studies of international migration, migrant worker, and subjective wellbeing (SWB) have been thoroughly examined.  However, the question on those subjects is still rarely developed when it comes to the particular circumstances. Given the problems, this study focuses on detailed settings such as blue-collar worker and non-procedural (NBMW). This study also aims to explore the perception of public, government, and workers about the issue: how the different perspective of legality, obligation, rights, and security differ among parties. It is important to understand the rationale between them to acquire the proper insight and formulate the best grasp. It is done by analysing the components of SWB (pleasant and unpleasant affect) and the coping mechanisms to deal with it. This study uses qualitative method and interview to gather the data in order to obtain maximal result. This study finds that international are able to change their perception about life. NBMW are able to alter their unpleasant affect to the pleasant ones by doing some sort of coping mechanisms. There is almost non-existent dysfunctional coping used. Most of them are using problem and emotional focused coping mechanism to deal with the problem. One of the reasons is their consideration of future planning for family left behind and themselves. International migration plays an important role despite their imperfection while doing it. International migration provides them positive aspects such elation and hope though negative aspects like sadness, and anxiety and worry are not necessarily absent.